Optimalisasi Pendidikan Keperawatan Berkelanjutan Melalui Implementasi Diskusi Refleksi Kasus (DRK) - Fatiyah Fatiyah; Rr. Tutik Sri Hariyati; Rusdiyansyah Rusdiyansyah (Jurnal Keperawatan Silampari, 2022)
This study aims to improve the ability to evaluate the results of reforming agents in implementing the Case Reflection Discussion program. The method used is a pilot study method using a problem-solving approach—the results of the problem identification need to be optimized for the implementation of CRD. Problem-solving begins with the preparation of guidelines and SOPs on CRD. The performance of CRD was piloted in 4 rooms; the results of the progress evaluation obtained after participating in CRD were nurses stated that CRD helped increase knowledge, critical thinking skills, spurring work according to standards and as a solution in solving problems in service. In conclusion, the implementation of CRD requires support from hospital management in the form of structuring the system and providing motivation and facilities. The performance of CRD needs to be supported and carried out through tiered supervision from the team leader, head of the room to the head of the nursing field. Keywords: Case Reflection Discussion (CRD), Continuing Nursing Education (CNE)